Enhancing Food Security in a Changing Climate in Africa - African Group of Negotiators Expert Support (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate and socio-ecological change scenarios are invaluable tools in developing appropriate response options for ensuring food security and human wellbeing in the future: evidence-based approach. Climate change necessitates research on crops, livestock and systems that are resilient to variability and extreme events. Prioritize and mainstream food security and nutrition issues into regional and national climate change adaptation and mitigation programmes and initiatives. Opportunities exist for the development of climate-proof and resilient food systems across Africa through technology diffusion, agronomic practices and innovations that can be optimized and scaled up.